2016
DOI: 10.20506/rst.35.3.2569
|View full text |Cite
|
Sign up to set email alerts
|

A contagious bovine pleuropneumonia outbreak on a research farm in Ethiopia, and its dynamics over an eight-month period

Abstract: Contagious bovine pleuropneumonia (CBPP) was recognised on Bako Agricultural Research Farm, in the Oromia Region of Ethiopia, for the first time on 5 May 2011. The outbreak was investigated by combining recognition of clinical signs, post-mortem examination, mycoplasma isolation and serological testing using competitive enzymelinked immunosorbent assay (c-ELISA). The clinical cases were monitored for eight months; sick animals were treated with a range of antibiotics and isolated if necessary. The outbreak of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kenyan farmers reported that treatment with tetracyclines often leads to relapse of the disease . More recently, among various antibiotic treatments used in a field outbreak in Ethiopia, only tylosin prevented disease relapses (Almaw et al, 2016), while danofloxacin treatment in Namibia resulted in an immediate drop in cases, with no further disease reported during a two-year period (Nicholas et al,2012).…”
Section: Pharmaceutical Availabilitymentioning
confidence: 99%
“…Kenyan farmers reported that treatment with tetracyclines often leads to relapse of the disease . More recently, among various antibiotic treatments used in a field outbreak in Ethiopia, only tylosin prevented disease relapses (Almaw et al, 2016), while danofloxacin treatment in Namibia resulted in an immediate drop in cases, with no further disease reported during a two-year period (Nicholas et al,2012).…”
Section: Pharmaceutical Availabilitymentioning
confidence: 99%
“…The infective Coenurus cerebralis cysts are then swallowed by sheep and goats (Scala and Varcasia, 2006;Sharma and Chauhan, 2006). CBPP is transmitted by infective aerosol inhalation of Mycoplasma mycoides mycoides (Almaw et al, 2016;Scott, 2014). Anthrax is a zoonotic disease caused by the Bacillus anthracis bacterium, which can be transmitted to humans through the consumption of infected carcasses or by handling infected animal products.…”
Section: Data Collectionmentioning
confidence: 99%